Integración de los precios en los canales minorista y mayorista arroz, papa y fríjol en la ciudad de Cali (2010)
Short and long run relations between wholesaler and retailer prices for rice, beans and potato in Cali, are studied using cointegration analysis, causality tests and VAR models in differences. It is found that the only integrated commercialization chain is the potato one. We found a causal relation from wholesaler to retailer for rice and potato, but from retailer to wholesaler for beans.